Imidazole-linked crystalline two-dimensional polymer with ultrahigh proton-conductivity - Ranjeesh, Kayaramkodath Chandran; Ilathvalappil, Rajith; Veer, Sairam Dnyaneshwar; Peter, Joseph; Wakchaure, Vivek Chandrakant; Goudappagouda; Raj, K. Vipin; Kurungot, Sreekumar; Babu, Sukumaran Santhosh (Journal of the American Chemical Society, 2019)
Proton-exchange membrane fuel cells are promising energy devices for a sustainable future due to green features, high power density, and mild operating conditions. A facile proton-conducting membrane plays a pivotal role to boost the efficiency of fuel cells, and hence focused research in this area is highly desirable. Major issues associated with the successful example of Nafion resulted in the search for alternate proton conducting materials. Even though proton carrier loaded crystalline porous organic frameworks have been used for protonconduction, the weak host-guest interactions limited their practical use. Herein, we developed a crystalline 2D-polymer composed of benzimidazole units as the integral part, prepared by the condensation of aryl acid and diamine in polyphosphoric acid medium. The imidazole linked-2D-polymer exhibits ultrahigh proton conductivity (3.2 X 10(-2) S cm(-1)) (at 95% relative humidity and 95 degrees C) in the pristine state, which is highest among the undoped porous organic frameworks so far reported. The present strategy of a crystalline proton-conducting 2D-polymer will lead to the development of new high performing crystalline solid proton conductor.

Donor strapped perylene bisimide macrocycle and its lemniscate dimer with extended charge separation - Veer, Sairam Dnyaneshwar; Goswami, Tanmay; Ravindranathan, Sapna; Gonnade, Rajesh; Kharbanda, Nitika; Ghosh, Hirendra N.; Babu, Sukumaran Santhosh (Inorganic Chemistry Frontiers, 2023)
Macrocyclic structures are fascinating due to their unique design and capability to place chromophores in specific orientations, resulting in exciting optoelectronic properties. However, the synthetic challenges limit the broad exploration of such systems. Herein, we report a thiophene-diacetylene-based ring strapped perylene bisimide macrocycle and its notably different electron transfer features. Single-crystal analysis of the macrocycle pointed to the nearly orthogonal placement of donor-acceptor units, facilitating better electronic communication between them. Interestingly, introduction of an alkyl substituent on the peripheral thiophene ring opened the possibility of forming a higher oligomer macrocycle consisting of two strapped perylene bisimide units. Diffusion and two-dimensional NMR experiments provided insight into the structure of the figure-eight-shaped lemniscate dimer. Transient absorption measurements showed faster electron transfer and extended stabilization of the charge-separated state. The thiophene-diacetylene-based ring is a better donor unit to facilitate rapid electron transfer and extended charge separation in the macrocycle and its lemniscate dimer. The new macrocycle design enables the formation of higher analogs equally capable of stabilizing the charge-separated state. Donor-acceptor (D-A) macrocycle designs position the respective units to achieve ultrafast electron transfer precisely and an extended charge-separated state. Here, we report a D-A macrocycle and its lemniscate dimer molecule with exciting electron transfer features.

Polymerizable solvent-free organic liquids: a new approach for large area flexible and foldable luminescent films - Wakchaure, Vivek Chandrakant; Veer, Sairam Dnyaneshwar; Nidhankar, Aakash D.; Kumar, Viksit; Narayanan, Aswini; Babu, Sukumaran Santhosh (Angewandte chemie-international editon, 2023)
The high demand for light-emitting and display devices made luminescent organic materials as attractive candidates. Solvent-free organic liquids are one of the promising emitters among them due to the salient features. However, the inherent limitations of forming sticky and noncurable surfaces must be addressed to become an alternate emitter for large-area device applications. Herein, we functionalized solvent-free organic liquids having monomeric emission in bulk with polymerizable groups to improve the processability. The polymerizable group on carbazole, naphthalene monoimide, and diketopyrrolopyrrole-based solvent-free liquid emitters enabled on-surface polymerization. These emitters alone and in combinations can be directly coated on a glass substrate without the help of solvents. Subsequent photo or thermal polymerization leads to stable, non-sticky, flexible, foldable, and free-standing large-area films with reasonably high quantum yield. Our demonstration of the tunable and white light-emitting films using polymerizable solvent-free liquids might be a potential candidate in flexible/foldable/stretchable electronics. The new concept of polymerizable liquid can be extended to other functional features suitable for futuristic applications.
Keywords: Energy Transfer; polymerization; Solvent-Free Organic Liquids; Thin-Film; White Light

Thermally activated delayed fluorescent solvent-free organic liquid hybrids for tunable emission applications - Nidhankar, Aakash D. D.; Goudappagouda; Kothavade, Premkumar D.; Dongre, Sangram D.; Veer, Sairam Dnyaneshwar; Dash, Soumya Ranjan; Rajeev, Kavya; Unni, K. N. Narayanan; Shanmuganathan, Kadhiravan; Babu, Sukumaran Santhosh (Chemistry-An Asian Journal, 2023)
The synthetic feasibility and excellent luminescence features of organic molecules attracted much attention and were eventually found useful in lighting applications. In this context, a solvent-free organic liquid having attractive thermally activated delayed fluorescence features in bulk along with high processability has prime importance. Herein, we report a series of naphthalene monoimide-based solvent-free organic liquids exhibiting cyan to red thermally activated delayed fluorescence with luminescence quantum yields up to 80% and lifetimes between 10 to 45 mu s. An effective approach explored energy transfer between liquid donors with various emitters exhibiting tunable emission colors, including white. The high processability of liquid emitters improved the compatibility with polylactic acid and was used for developing multicolor emissive objects using 3D printing. Our demonstration of the thermally activated delayed fluorescence liquid will be much appreciated as a processable alternate emissive material suitable for large-area lighting, display, and related applications.
Keywords: 3D printing; Energy Transfer; OLED; Organic Liquids; TADF

Orthogonally Engineered Redox-Active Polyimide-Carbon Nanotube Hybrids for Long-Life Lithium-Ion Battery Cathode - Thanasekar, Chandragopal; Javaregowda, Bharathkumar H.; Veer, Sairam Dnyaneshwar; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2026)
The diverse structural tunability and engineered electronic properties of organic polymers have sparked significant interest in their use as cathode materials for lithium-ion storage. Recent advances suggest that organic cathodes can serve as promising alternatives to conventional metal oxide counterparts due to their elemental abundance, safety, and high theoretical capacity. However, developing cathode materials that simultaneously exhibit high specific capacity, long cycle life, and excellent rate performance remains a critical challenge. In this study, the synthesis and application of a redox-active polyimide based on orthogonally positioned, active site-rich mellitic trianhydride (MTA) and naphthalene diimide (NDI), integrated with multi-walled carbon nanotubes (MWCNTs), referred to as MTA-NDI@CNT are reported. The pristine MTA-NDI polymer demonstrates a specific capacity of 60 mAh g-1 at a current density of 200 mA g-1 and exhibits remarkable cycling stability over 20 000 cycles. Upon hybridisation with CNT (10 wt.%), the composite (MTA-NDI@CNT) delivers a nearly threefold enhancement in specific capacity, reaching 170 mAh g-1 at 500 mA g-1, along with stable cycling performance over 1300 cycles and 60.5% capacity retention.
Keywords: cathode; CNT; lithium-ion battery; orthogonality; Polyimide